GPS data from Ocean nomads or island specialists? Culturally driven habitat partitioning contrasts in scale between geographically isolated sperm whale populations - Felicia Vachon; Taylor A. Hersh; Luke Rendell; Shane Gero; Hal Whitehead (2022)
GPS coordinates of the research vessel used for distribution map